DOI: 10.11606/t.47.2010.tde-08092010-150927
|View full text |Cite
|
Sign up to set email alerts
|

Análise da aquisição de comportamento verbal em uma criança dos dezoito meses aos dois anos de idade

Abstract: The purpose of the present study is to investigate the acquisition of verbal behavior in a longitudinal research with a typical development child from eighteen months of age until two years old, adopting as unit of analysis Skinner´s (1957) verbal operants. The aim of the present work is to analyze verbal responses emitted by the child and the caretakers in a natural setting in terms of verbal operants and try to identify relations between the emission of operants by caretakers and the child, investigating pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…This combination of factors may have contributed to the effectiveness of the vocal tact teaching procedure and establishment of this repertoire, which is in line with the results of studies that examined the adult role in proposing appropriate learning conditions for children (Cruvinel, 2010).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This combination of factors may have contributed to the effectiveness of the vocal tact teaching procedure and establishment of this repertoire, which is in line with the results of studies that examined the adult role in proposing appropriate learning conditions for children (Cruvinel, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…Several studies have analyzed the role of the adult in proposing appropriate teaching conditions (Cruvinel, 2010;Gil, Oliveira, Sousa, & Faleiros, 2006;Greer & Ross, 2008;LeBlanc et al, 2009;Sousa, Souza, & Gil, 2013), planning the teaching so that the child is exposed to the stimulus for a determined number of times (Antoniazzi, Domeniconi, & Schmidt, 2014;Gurteen, Horne, & Erjavec 2011;Sousa et al, 2013) and also as a provider of the conditions subsequent to the response(s) that are reinforcers (Gil, Oliveira, & McIlvane, 2011;Sousa, Garcia, & Gil, 2014). In the study reported here, the adult that proposes appropriate teaching conditions is represented by the researcher, who adopted a favorable method for the study and, simultaneously, needed to consider the requirements of the target population, since they were children at risk of social vulnerability.…”
mentioning
confidence: 99%